2013
DOI: 10.1007/s12079-013-0201-y
|View full text |Cite
|
Sign up to set email alerts
|

CCN2/CTGF is required for matrix organization and to protect growth plate chondrocytes from cellular stress

Abstract: CCN2 (connective tissue growth factor (CTGF/CCN2)) is a matricellular protein that utilizes integrins to regulate cell proliferation, migration and survival. The loss of CCN2 leads to perinatal lethality resulting from a severe chondrodysplasia. Upon closer inspection of Ccn2 mutant mice, we observed defects in extracellular matrix (ECM) organization and hypothesized that the severe chondrodysplasia caused by loss of CCN2 might be associated with defective chondrocyte survival. Ccn2 mutant growth plate chondro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 52 publications
4
30
0
Order By: Relevance
“…Further, we examined the expression of ATG5 and FGFR3 in the tibia growth plate from postnatal d 5 WT mice. Consistent with the expression pattern of ATG12 reported in a previous study, 29 we found that immunoreactive ATG5 particles were observed mainly in cells in the proliferative, prehypertrophic and hypertrophic zones, which were overlapped with the expression of FGFR3 (Fig. 6E).…”
Section: Fgfr3 Interacts With the Atg12-atg5 Conjugate In Cells And Isupporting
confidence: 91%
See 2 more Smart Citations
“…Further, we examined the expression of ATG5 and FGFR3 in the tibia growth plate from postnatal d 5 WT mice. Consistent with the expression pattern of ATG12 reported in a previous study, 29 we found that immunoreactive ATG5 particles were observed mainly in cells in the proliferative, prehypertrophic and hypertrophic zones, which were overlapped with the expression of FGFR3 (Fig. 6E).…”
Section: Fgfr3 Interacts With the Atg12-atg5 Conjugate In Cells And Isupporting
confidence: 91%
“…20,59 Impaired autophagy is involved in the pathogenesis of chondrodysplasia resulting from the loss of Sumf1 or Ctgf/Ccn2, in which, chondrocyte viability is profoundly reduced because of the lack of protection from autophagy. 28,29 As the most common genetic form of dwarfism in humans, achondroplasia is characterized by the retarded bone growth with strongly impaired cell viability, including inhibited proliferation, delayed differentiation and increased apoptosis. 12,60,61 The phenotype similarity between mice with ACH and loss of Sumf1 or Ctgf/Ccn2 suggests that impaired autophagy may play a role in the pathogenesis of achondroplasia as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCN2 is principally produced by chondrocytes immediately before their hypertrophic differentiation, is transported from the chondrocytes to target cells and indeed promotes all of the processes that operate for endochondral ossification [1,49,50], which is typically represented by the phenotype observed in Ccn2null mice with remarkable skeletal defects [1,49,51]. Two other recent reports indicate such a role of CCN2 in intervertebral disc development and palatogenesis as well [52,53].…”
Section: Skeletal Developmentmentioning
confidence: 99%
“…This particular CCN family member plays significant roles in physiological development [7][8][9][10][11][12][13][14][15], wound healing [16], and in the pathological fibrotic remodeling of multiple tissues, organs [17][18][19][20][21][22][23][24][25][26][27][28], and malignancies throughout the body [3,5]. CCN2 is required for the proper development of the olfactory central nervous system [29], pancreas [30], hair follicles [31], and skeletal system [11]; hence, Ccn2-null mice die upon delivery [32,33]. CCN2 is also known to be involved in multiple steps of orofacial development [34,35].…”
mentioning
confidence: 99%